Problems of ensuring the consistency of legal terms in the Special Part of the Civil Code of the Republic of Kazakhstan - Myrzaliyeva, Zh.T.; Akimzhanova, M.T. (Bulletin of the Karaganda University “Law Series”, 2022)
One of the main goals of lawmaking activities in any state is to ensure the quality and stability of legal acts adopted in the country. The issues related to the examination of the Kazakh and Russian versions of the text of Special Part of the Civil Code of the Republic of Kazakhstan are considered in the article. In the sphere of civil law attention is drawn to the texts of legal norms in the state language, compliance with the sequence of legal terms. The purpose of the research is to identify errors in the translations of law based on the analysis of the texts of civil law in the state language, since an example is a low-quality version of daily enactments in the state language. The authors expressed an opinion on the application of legal terms introduced from a foreign language in the national legislation, in its original form without translation into Kazakh. In addition, the article gives a generalization on issues of low-quality translating texts of legislative acts to the Kazakh language, on the basis of which conclusions are drawn on the improvement of legal writing on the development of legislative acts in the state language, since the necessary condition for legal writing is to comply with the uniformity of terminology and prevent the use of several terms related to one concept. The results of the examination will serve as the basis for the authors of the «Unique dictionary of legal terms in the Kazakh language». The general methods of scientific knowledge: synthesis, analysis, induction, deduction, comparative legal, systemic, logical methods are used in the article.